Assistance with Pagersari Governance to Become a Smart Village with Administration and Financial Management - Izzalqurny, Tomy Rizky; Fauzan, Slamet; Muhammad, Muhammad; Ferdiansyah, Rifaldy Adinandra (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of this service is to assist Pagersari Village in improving its administrative and financial governance, with the ultimate goal of transforming it into a Smart Village. Despite having excellent potential, Pagersari Village faces challenges in optimizing its administrative and financial aspects. Method: A series of assistance activities were carried out from June to September 2023. The main activities included the preparation of efficient and transparent village administration management guidelines and assistance with an integrated financial system. Additionally, village staff were trained in good administrative management and the use of the autocrat application. Practical Applications: The practical application of this service is the creation of a transformation plan for Pagersari towards becoming a Smart Village. This plan focuses on more efficient, transparent, and technology-based administrative and financial management. Conclusion: The successful implementation of this service in Pagersari Village serves as an example for other villages. It demonstrates the feasibility of realizing Smart Villages as part of sustainable development efforts at the village level. This success story can inspire and guide other villages in their journey towards becoming Smart Villages.